Methanolysis of poly(3‐hydroxybutyrate) catalyzed by ferric chloride. Issue 8 (8th March 2018) - Song, Xiuyan; Wang, Chan; Shen, Yong; Liu, Fusheng; Yu, Shitao; Ge, Xiaoping
Abstract: Methanolysis of poly(3‐hydroxybutyrate) (PHB) was investigated using ferric chloride (FeCl3 ) as catalyst. The structures of the obtained product were characterized by FT‐IR and 1 H NMR, and it was indicated that the main product was methyl 3‐hydroxybutyrate (M3HB). The effects of reaction temperature, reaction time, and the amounts of methanol and catalyst on the conversion of PHB and yield of M3HB were investigated. Under optimum conditions, the conversion of PHB and yield of M3HB were 91.1% and 88.3%, respectively. The catalyst could be reused six times with no apparent decrease in its catalytic activity. Kinetic study indicated that this reaction was a first‐order kinetic reaction with activation energy of 34.17 kJ/mol. Moreover, the possible mechanism of the reaction was proposed.